2013
DOI: 10.1016/j.ihj.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein lipase gene HindIII polymorphism and risk of myocardial infarction in South Indian population

Abstract: Our study strongly suggests that the LPL gene HindIII Hþ Hþ genotype is an independent risk factor for first MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…We could observe that as previous studies, in this study, there were associations between demographic risk factors (smoking, hypertension, hyperlipidemia, TG> 200 mg/dl and HDL<40 mg/dl) and CAD. 2 , 9 , 12 , 14 , 15 These risk factors were due to the increase in the susceptibility to CAD. Smoking had the most influence on this disease ( smoking: P <0.001, OR=3.256, 95% CI=1.781-5.953; hypertension: P =0.025, OR=1.952, 95% CI=1.086-3.508; hyperlipidemia: P =0.004, OR=2.347, 95% CI=1.315-4.189; TG>200 mg/dl: P =0.004, OR=2.345, 95% CI=1.321-4.161; HDL<40 mg/dl: P =0.024, OR=1.917, 95% CI=1.090-3.372).…”
Section: Discussionmentioning
confidence: 99%
“…We could observe that as previous studies, in this study, there were associations between demographic risk factors (smoking, hypertension, hyperlipidemia, TG> 200 mg/dl and HDL<40 mg/dl) and CAD. 2 , 9 , 12 , 14 , 15 These risk factors were due to the increase in the susceptibility to CAD. Smoking had the most influence on this disease ( smoking: P <0.001, OR=3.256, 95% CI=1.781-5.953; hypertension: P =0.025, OR=1.952, 95% CI=1.086-3.508; hyperlipidemia: P =0.004, OR=2.347, 95% CI=1.315-4.189; TG>200 mg/dl: P =0.004, OR=2.345, 95% CI=1.321-4.161; HDL<40 mg/dl: P =0.024, OR=1.917, 95% CI=1.090-3.372).…”
Section: Discussionmentioning
confidence: 99%
“…Several polymorphisms in the LPL gene have been shown to lead to a reduction in enzyme synthesis and activity and, to date, rs320 [ HindIII (G/T)] and rs328 [ Serine 447 Stop S447X (C/G)] have been the most extensively studied. These variants with a prevalence of 40%–75% (rs320) and 17%–22% (rs328) among Caucasians [ 8 , 9 ], respectively, have been shown to be associated with coronary artery disease, myocardial infarction [ 10 , 11 , 12 ] and pronounced fasting hypertriacylglycerolemia [ 13 , 14 ]. Only limited number of studies has examined their impact on postprandial lipaemia [ 15 , 16 , 17 ] and these studies have used only a single test meal, which does not reflect the habitual eating pattern in humans.…”
Section: Introductionmentioning
confidence: 99%
“…H¯allele was associated with lower levels of triglycerides and higher HDL-c in a southern Brazilian population of European descent and also the H¯ haplotypes was associated with a significant protective effect against in coronary artery disorders in male subjects 64 . Similar results, like LPL H + H + genotype, was a risk factor for myocardial infarction in Brazil and Russian population 65 and significantly associated with myocardial infarction (MI) patients in South Indian population 66 , but these polymorphic studies are very limited in India. In another study observed H¯ (G) allele was not associated with blood lipids or cardiovascular events 67 and also a recent study conducted by Marcia et al reported H + /H + (T/T) genotype and the H + (T) allele were associated with elevated VLDLc and triglycerides levels (P < 0.05) and reduced HDL-C levels (P < 0.05) 68 .…”
Section: Atherogenic Ratios Like Castelli's Risk Index-i (Cri-i)mentioning
confidence: 67%